The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of silver nanoparticles against Staphylococcus aureus - Prashik Parvekar; Jayant Palaskar; Sandeep Metgud; Rahul Maria; Smita Dutta (Medical Journals Sweden, 2020)
Aim To determine the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of silver nanoparticles against Staphylococcus aureus (S. aureus). Methodology: The antimicrobial efficacy of the silver nanoparticles was determined by the standard methods of Clinical and Laboratory Standards Institute (CLSI). Different concentrations of silver nanoparticles were prepared, and MIC was calculated by tube macro-dilution method. The MBC was determined by the lowest concentration that kills 99.9% of the initial bacterial population. The data were analyzed by ANOVA and Tukey's post hoc test using SPSS software. Results The MIC and MBC of silver nanoparticles against S. aureus was found to be 0.625 mg/ml. Conclusion The result obtained from this study shows that silver nanoparticles have potential bactericidal effects against S. aureus at a concentration of 0.625 mg/ml. Silver nanoparticles can be incorporated in the root canal medicaments, sealers and irrigants as it possess potent antimicrobial efficacy against S. aureus.